Uudistuva sosiaali- ja terveysala - Hujala, Anneli; Taskinen, Helena (Tampere University Press, 2020)
"This research-based edited volume offers a clear, multifaceted and practical overview of the Finnish health and social care sector trends in the 2020s. The health and social care reform is again current as new ways of organising the sector are being developed on the foundation of the reform that fell through in spring 2019. The book introduces the Finnish health and social care services reform from three perspectives. The first part of the book looks at the sector from a macro perspective, that is, from the perspective of the service system reform. The articles deal with a historical overview of previous reforms, integration, and research on effectiveness and cost-effectiveness. The second part focuses on the organisational level issues such as reform of management and know-how and the challenges digitalisation poses for the health and social services. The third part of the book centres on the perspective of the people who implement the changes. The themes of the articles include care workers' multi-actor collaboration, person-centred case management and client involvement. The book is based on research done at the University of Eastern Finland as well as Finnish and international research literature. The authors represent various disciplines: health and social management, social work, social psychology and other social sciences and law. The book is aimed at managers and professionals, experts, decision makers, researchers and teachers in the field of health and social care. It is also suitable as a textbook for management studies at the university level."